TRY TO ANALYZE THE APPLICATION OF MIXED LEARNING MODE IN CHINESE TEACHING IN PRIMARY SCHOOL - Zhu Chunyu; Tan Tiam Lai (Journal of Islamic, Social, Economics and Development, 2024)
As a kind of teaching mode integrating traditional teaching and modern scientific and technological means, mixed learning mode has been gradually applied in primary school Chinese teaching. This paper tries to analyze the application of mixed learning mode in primary school Chinese teaching, aiming to explore the influence of this mode on students' Chinese learning and its feasibility in teaching practice.